Pain in Decreased Consciousness Patients - Masita; Rachman Toyo; Ika Erna Uly Sirait (HM Publisher, 2021)
The International Association for the Study of Pain (IASP) defines pain as an unpleasant sensory and emotional experience associated with potential or tissue damage or described in terms of such damage. Pain in patients with decreased consciousness is individual and needs to consider many aspects. Following the expansion pain definition according to the IASP in 2020, the inability to communicate does not exclude the possibility that humans experience pain. Therefore, a good pain assessment in patients with decreased consciousness can increase the value of disease management and improve the patient's quality of life both during the treatment period and after hospitalization. Because of the inability of patients with decreased consciousness to verbally convey their pain, this poses a challenge for the clinician. This literature review was aimed to describe how to understand the pain in decreased consciousness patients.